Accommodation of Islamic Education Responding to Local Culture - Suheri Sahputra Rangkuti; Sangkot Sirait; Moh Soehadha (AL-TAHRIR, 2021)
Abstract: the social reality in Indonesia shows that there is often friction between the understanding of Islam and local culture. This friction is thought to be strong as a result of idealizing Islam as an answer to all kinds of life problems, especially those related to social and cultural. This idealization stems from Islamic education reasoning that is still reasoned fiqh. This article was written to offer a new perspective (paradigm) in Islamic education to accommodate local culture in a balanced manner. Because so far, Islamic education still positions local culture as an object that is functioned to submit under Islamic interests (non-dialogist). The type of research used in this article is library research with a philosophical-paradigmatic analysis approach. In this case, Islamic education is seen in the historical dynamics of Islamic education thought and its interaction with local culture. Then deal with it with a logical approach maqasid. The results of this study at least provide some offers of change, namely, (1) changes in the value base of Islamic education from scriptural-theological to universal humanism, (2) changes in the vision of Islamic education from Islamist-symbolic to substantive Islamic values, (3) dialogist-based learning methods.الملخص: في الواقع الاجتماعي في إندونيسيا غالبا ما يكون هناك احتكاك بين فهم الإسلام والثقافة المحلية. ويعتقد أن هذا الاحتكاك قوي نتيجة إضفاء الطابع المثالي على الإسلام كإجابة على جميع أنواع المشاكل الحياتية، ولا سيما تلك المتعلقة بالمشاكل الاجتماعية والثقافية. وينبع هذا المثالية من منطق التعليم الإسلامي الذي لا يزال معللا بالفقه. كتب هذا المقال من أجل تقديم منظور جديد (نموذج) في التربية الإسلامية لاستيعاب الثقافة المحلية بطريقة متوازنة. لأنه حتى الآن، لا يزال التعليم الإسلامي يعتبر الثقافة المحلية هدفا يعمل على تقديمه وفقا للمصالح الإسلامية (غير الحوار). نوع البحث المستخدم في هذه المقالة هو أبحاث المكتبة مع نهج التحليل الفلسفي النموذجي. في هذه الحالة، ينظر إلى التعليم الإسلامي في الديناميات التاريخية للفكر الإسلامي التعليمي وتفاعله مع الثقافة المحلية. ثم التعامل معها مع نهج منطقي مقاصدية. تقدم نتائج هذه الدراسة على الأقل بعض عروض التغيير، وهي (1) التغيرات في قاعدة قيمة التعليم الإسلامي من الكتابية اللاهوتية إلى الإنسانية العالمية، (2) التغيرات في رؤية التعليم الإسلامي من القيم الإسلامية الرمزية إلى القيم الإسلامية الفرعية، (3) أساليب التعلم القائمة على الحوار.Abstrak: Realitas sosial di Indonesia menunjukkan bahwa sering kali terjadi gesekan antara pemahaman Islam dengan budaya lokal. Gesekan ini diduga kuat akibat dari mengidealisasi Islam sebagai jawaban atas segala macam persoalan hidup terutama yang menyangkut dengan sosial dan budaya. Idealisasi ini bersumber dari nalar pendidikan Islam yang masih bernalar fiqh. Artikel ini ditulis dalam rangka menawarkan cara pandang baru (paradigma) dalam pendidikan Islam untuk mengakomodasi budaya lokal secara berimbang. Sebab selama ini, pendidikan Islam masih memposisikan budaya lokal sebagai objek yang difungsikan untuk tunduk di bawah kepentingan Islam (non-dialogis). Jenis penilitian yang digunakan dalam artikel ini adalah library research dengan pendekatan analisis filosofis-paradigmatik. Dalam hal ini pendidikan Islam dilihat dalam dinamika sejarah pemikiran pendidikan Islam dan interaksinya dengan budaya lokal. Kemudian menyikapinya dengan pendekatan nalar maqasid. Hasil kajian ini setidaknya memberikan beberapa tawaran perubahan yaitu, (1) perubahan basis nilai pendidikan Islam dari skriptual-teologis ke humanisme-universal, (2) perubahan visi pendidikan Islam dari islamis-simbolis ke nilai Islam secara subtantif, (3) metode pembelajaran berbasis dialogis.